EFL Studentsâ Perspectives of Applying CALL through Project-Based Learning - Haryati, Haryati (UICELL, 2017)
Technology is everywhere in education. Schools, universities, and other educational institutions have provided computers for learners to run their learning activities. Most students enthusiastically welcome such an extraordinary technology. Moreover, the growth of technology encourages teachers to apply it in teaching learning process and involves learners in order to achieve the goals. Due to these issues, this study was conducted to determine studentsâ perspective on the implementation of Project Based Learning (PBL) activities in an application of Computer Assisted Language Learning (CALL). This study involved 40 participants who were learning writing at the fifth semester. To obtain the data, the writer distributed the paper-based Linkert scale survey, and the students handed the reflective notes in to answer two questions related to the implementation of PBL: What are the advantages of the PBL activities done in the CALL application? and What are the challenges of the PBL activities done in the CALL classroom?. The data analysis revealed that the students had positive responses on CALL and PBL in teaching and learning process although they found some obstacles to integrate CALL. The implication of CALL in learning English as a Foreign Language (EFL) can be used for further research.